Tone and content analysis in the president’s letters to shareholders: Spanish evidence - Bonsón, Enrique; Perea-Khalifi, David; Azevedo, Graça (Ural State University of Economics, 2021)
This article explores the potential factors that might be influencing the length and tone of the discourse of the IBEX35 presidents’ letters to shareholders. It also provides an analysis of their content. The methodological framework of the research relies on the impression management theory, that is, how companies want to present themselves, in a way that contributes to their goals. The research uses an automatic process of textual analysis, through R and Voyant Tools. For tone and length analysis, we used a total of 187 letters corresponding to the years 2013–2018, and for content analysis, a larger sample of 321 letters corresponding to the years 2008–2018. According to the research findings, there was a greater positive tone when the profits after taxes decreased and when the directors’ remuneration increased with respect to the previous year. Regarding content, the research shows that there are differences between non-financial and financial companies. In conclusion, our findings, which show that in certain situations the tone of discourse changes, are supported by and contribute to impression management theory. The study may be of interest to shareholders to better understand the content of the chairpersons’ letters.
Keywords: Análisis del discurso; Content analysis; Positive tone; Text mining; Financial report